PENDUKUNG PEREKONOMIAN MASYARAKAT MELALUI PEMANFAATAN BANK SAMPAH - Lora Ekana Nainggolan; Darwin Lie; Nana Triapnita Nainggolan; Ady Inrawan; Erbin Chandra (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
In human life, garbage becomes a phenomenon that will always exist as long as humans live and move, therefore garbage needs to be handled seriously and intersively. Garbage in people's lives can have negative and positive consequences, where the positive impact is that it can become manure, as a livelihood for scavengers, as well as as one of the elements in the manufacture of energy, or fuel. While the negative impact is that garbage can cause the spread of disease, as well as ecological damage, the number of floods due to garbage accumulation in rivers close to the population and others. Garbage can be managed by involving all parties, such as the community, government, and other institutions. Garbage can also be reduced in people's lives by composting, replacing burning, reusing, recycling.